A multi‐state initiative to implement pediatric oral health in primary care practice and clinical education. (7th June 2017) - Silk, Hugh; Sachs Leicher, Ellen; Alvarado, Veronica; Cote, Elizabeth; Cote, Susan
Abstract: Objectives: To implement and study the effect of improving pediatric oral health by training primary care practices and training programs. Method: In six New England States, primary care practices and clinical training programs (medical schools, residencies, physician assistant programs) were recruited and trained to incorporate pediatric oral health into medical practice. We measured the results of varying practice recruitment approaches and measured training outcomes based on self‐reported implementation and state reported EPSDT CMS oral health claims. Results: We trained 415 practices across six states with a 74 percent average retention rate of providing services at 6 months. This resulted in 136, 963 preventive oral health services (fluoride varnish, oral health assessment, or screening). Thirty‐five of 52 health education programs established pediatric oral health curricula. The average cost of recruitment, training, and follow‐up for an office or an educational program is approximately 1, 000/site. Conclusion: We have created an enduring infrastructure and model for primary care practices and education programs for training in pediatric oral health.